2013
DOI: 10.1186/1559-4106-8-27
|View full text |Cite
|
Sign up to set email alerts
|

Adherent cells avoid polarization gradients on periodically poled LiTaO3 ferroelectrics

Abstract: The response of fibroblast cells to periodically poled LiTaO3 ferroelectric crystals has been studied. While fibroblast cells do not show morphological differences on the two polarization directions, they show a tendency to avoid the field gradients that occur between polarization domains of the ferroelectric. The response to the field gradients is fully established after one hour, a time at which fibroblasts form their first focal contacts. If suspension cells, with a lower tendency to establish strong surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Indeed, previous studies have shown that fibroblasts preferentially adhere to positively charged surfaces. [24] Seeding of primary fibroblasts on polarized and pristine PVDF-TrFE substrates revealed no difference in morphology of the human primary fibroblasts in accordance with findings of Christofis et al [18] where rat embryonic fibroblasts did not show preference of either polarization of a LiTaO3 substrate in a side by side comparison on a patterned surface, but the cells avoided polarization gradients between the polarization domains. Some negatively charged polymer surfaces have been shown to negatively affect cell adhesion [25] and cell binding proteins.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Indeed, previous studies have shown that fibroblasts preferentially adhere to positively charged surfaces. [24] Seeding of primary fibroblasts on polarized and pristine PVDF-TrFE substrates revealed no difference in morphology of the human primary fibroblasts in accordance with findings of Christofis et al [18] where rat embryonic fibroblasts did not show preference of either polarization of a LiTaO3 substrate in a side by side comparison on a patterned surface, but the cells avoided polarization gradients between the polarization domains. Some negatively charged polymer surfaces have been shown to negatively affect cell adhesion [25] and cell binding proteins.…”
Section: Discussionsupporting
confidence: 85%
“…Ferroelectric surfaces, with defined polarization patterns, have been proposed as substrates to guide the growth patterns of cell cultures. [16][17][18]These surfaces provide a well-defined surface charge when polarized in an aqueous environment as the charge is fixed on the surface, resulting in non-faradaic charging. [19,20] In an electrode/ferroelectric film/aqueous electrolyte/electrode configuration (Figure 1), the state of the ferroelectric film can undergo a phase transition upon electric biasing.…”
Section: Introductionmentioning
confidence: 99%
“…19) and PPLT. 29 The results point to promising research directions exploiting LiNbO 3 as a neural substrate. Potentially, these can be combined with further control and sensing capabilities afforded by the photonic and piezoelectric properties of this material, already widely used for the nonlinear optical frequencyconversion of conventional lasers and to generate standing 31 and traveling 32 surface acoustic waves for sorting particles or cells in flow channels.…”
Section: à2mentioning
confidence: 99%
“…On these substrates, axons appeared to recognize and align with domain boundaries, reminiscent of the avoidance of domain boundaries by fibroblasts on a periodically poled lithium tantalate (PPLT). 29 To check if there was a preferential deposition of the positively charged PLL to negatively charged domains, we coated the substrate with fluorescein isothiocyanate-conjugated PLL (FITC-PLL; Sigma); however, no preferential deposition was detected ( Fig. 2(a), inset).…”
mentioning
confidence: 99%
“…Given the propensity for the LN surface to influence molecular adsorption, selective deposition, and so forth, it is hypothesized that the LN surface charge may influence cell proliferation provided that LN is biocompatible. Recently, LN powders have been reported to exhibit bioactivity and LiTaO 3 crystals and porous piezoelectric lithium sodium potassium niobate ceramics have been reported to demonstrate cytocompatibility with fibroblasts and osteoblasts, respectively. Nevertheless, biocompatibility has yet to be established for LN crystals, and the role of the polarization has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%